Upaya Meningkatkan Pemahaman Materi Jinayah dalam Pembelajaran Fikih menggunakan Metode Role Playing - Tri Nur Utami Agustina; Dede Rizal Munir; Usep Setiawan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This classroom action research was conducted to improve the speaking skills of eleventh-grade students of Islamic high school in the subject of Islamic jurisprudence, especially in the Jinayah material. The problems that emerged in the class were that most students were still passive, lacked self-confidence, and were not yet able to express their opinions clearly and coherently. To overcome this, a role-playing learning model was used that emphasized role-playing activities so that students were more active, brave, and trained to speak in front of their friends. The research was conducted using the Kurt Lewin model which includes the stages of planning, implementation, action, observation, and reflection. The research subjects were 24 eleventh-grade students. Data were collected through questionnaires and documentation, with assessment instruments that emphasized aspects of voice clarity, courage, fluency, accuracy of Islamic jurisprudence terms, and expression. The results of the study showed an increase in students' speaking skills from the initial conditions to the implementation of the second cycle. The application of the role-playing model has been proven to be an alternative strategy for effective Islamic jurisprudence learning, while providing a more meaningful learning experience for students.